Physico-chemical, heavy metal analysis and physical composition of household solid waste, Shone Town, Ethiopia - GIZACHEW BALILO; ABEBE ASCHALEW; REJILA MANIKANDAN; ARBO FEYISA (Smujo International, 2023)
Abstract. Balilo G, Aschalew A, Manikandan R, Feyisa A. 2023. Physico-chemical, heavy metal analysis and physical composition of household solid waste, Shone Town, Ethiopia. Nusantara Bioscience 15: 32-37. In Ethiopia, Shone is one of the country's fast-developing towns; inadequate solid waste management was observed. Therefore, the objective of the study was to determine the generation rate and selected physico-chemical characterization and heavy metal analysis of household solid waste. The study was conducted on randomly selected 120 households from two Kebele of the town. The physico-chemical analysis results revealed that moisture content, pH, electrical conductivity (dS/cm), nitrogen, organic carbon, (%), phosphorus and potassium content of household solid waste were 54.6, 8.25, 2.52 (dS/cm), 2.47, 10.25, 0.54, and 0.82%, respectively. In addition, in the decomposed household solid waste samples, heavy metals such as iron, manganese, copper, zinc, nickel, cobalt, chromium, lead, and cadmium were analyzed using atomic absorption spectrophotometer. Results showed the concentration of these heavy metals in the decomposed solid waste samples was in the order of iron>manganese>zinc>copper>nickel>chromium>cobalt>lead>cadmium. Daily solid waste from those households was separated into its components, and each component was measured. That was conducted for 7 consecutive days to quantify and characterize household solid waste. The result revealed that the household solid waste generation rate in the study area was 0.206 kilogram/capita/day. The physical composition of the solid waste in Shone Town is mainly organic, constituting 92.8%. The organic waste of the town has a high content of biodegradable waste such as food waste (49.56%), ash and dust (29.74%), yard waste (4.95%), textile (4.006%), old shoes and bone (2.5%), paper and cardboard (2.04%) and recyclable material such as plastic (3.28%), glass and metal (3.88%) all account for 92.8% (biodegradable) and 7.17% (non-biodegradable), respectively.